High Efficiency Class-F Rectifier Based on Harmonic-Controlled Voltage Doubler With Extended Input Power and Frequency Range - Jaemin Shin; Juntaek Oh (IEEE Journal of Microwaves)
This paper presents a highly efficient class-F rectifier based on a harmonic-controlled voltage doubler (HCVD) structure. Previous studies on voltage doubler-based class-F rectifiers, have primarily configured the harmonic termination network only at the RF input port and the DC output port. In this design, the proposed HCVD comprises a voltage doubler and T-shaped harmonic control network (HCN) connected to each diode of the voltage doubler. The T-shaped HCN can independently manipulate the 2nd and 3rd harmonics of the voltage and current across each diode, thus achieving high efficiency even at low input power compared to the input power with maximum efficiency. Since it can also move the input impedance of the HCVD to the load impedance by adjusting the widths of the three transmission lines without additional matching network, the proposed rectifier can achieve high efficiency across a wide input power and frequency range. The proposed rectifier was implemented with a size of 34.7 mm × 29.7 mm. The measurement results also show that it achieves a peak power conversion efficiency (PCE) of 79 % at 27.2 dBm of input power at 2.45 GHz. The measured PCE was maintained over 50% within an input power range of 6.9–30.0 dBm at 2.45 GHz and a frequency range of 1.55–2.75 GHz at 27 dBm of input power.